Kinematic Boundary Conditions Favouring Subduction Initiation at Passive Margins Over Subduction at Mid-oceanic Ridges - Auzemery, A.; Willingshofer, E.; Yamato, P.; Duretz, T.; Beekman, F. (Frontiers in Earth Science, 2021)
We perform numerical modelling to simulate the shortening of an oceanic basin and the adjacent continental margins in order to discuss the relationship between compressional stresses acting on the lithosphere and the time dependent strength of the mid-oceanic ridges within the frame of subduction initiation. We focus on the role of stress regulating mechanisms by testing the stress–strain-rate response to convergence rate, and the thermo-tectonic age of oceanic and continental lithospheres. We find that, upon compression, subduction initiation at passive margin is favoured for thermally thin (Palaeozoic or younger) continental lithospheres (<160 km) over cratons (>180 km), and for oceanic basins younger than 60 Myr (after rifting). The results also highlight the importance of convergence rate that controls stress distribution and magnitudes in the oceanic lithosphere. Slow convergence (< 0.8 cm/yr) favours strengthening of the ridge and build-up of stress at the ocean-continent transition allowing for subduction initiation at passive margins over subduction at mid-oceanic ridges. The results allow for identifying geodynamic processes that fit conditions for subduction nucleation at passive margins, which is relevant for the unique case of the Alps. We speculate that the slow Africa – Europe convergence between 130 and 85 Ma contributes to the strengthening of the mid-oceanic, leading to subduction initiation at passive margin 60-70 Myr after rifting and passive margin formation.